(untitled) (Indonesian Sports Justice Review, 2024)
Gender discrimination in sports remains a significant issue in Indonesia, where women and girls face systemic obstacles to participation, advancement, and recognition in athletics. This paper investigates the persistent barriers to gender equity in Indonesia’s sports landscape, focusing on discriminatory practices at both grassroots and elite levels. Using a combination of interviews with female athletes, coaches, and sports administrators, alongside an analysis of policy documents, the study uncovers how cultural norms, limited funding, and institutional biases contribute to gender-based disparities in sports. The research also explores how women’s sports have been historically undervalued in terms of media representation, sponsorship, and leadership opportunities. This paper argues for the need for a multi-faceted approach to combat gender discrimination, including reforms to sports education, better media coverage of women’s sports, and legal protections for female athletes. The findings advocate for a cultural shift that recognizes and values the contributions of women in sports.